THE INFLUENCE OF THE VESPA SPEEDING INDONESIA YOUTUBE CHANNEL ON SUBSCRIBER LIFESTYLE - Maulana, Rifki; Agustiningrum, Henny; Puspadarmaja, Nyoman (Transpublika Publisher, 2023)
The development of technology has resulted in social media becoming an online tool that allows individuals and groups to share digital content. Among the various forms of social media, vlogs (video blogs) and YouTube stand out as platforms that offer information through a combination of images, sound, video, and text. YouTube, in particular, is widely used by people for informational purposes and features diverse channels spanning various topics, including music, travel, culinary arts, and automotive enthusiasts. Piaggio's Vespa, known as a legendary brand, is one of many brands that offer Vespa products. As a pioneer in the automotive industry, Vespa chose to launch a YouTube Channel called Vespa Ngebut Indonesia, dedicated to Vespa riders in Indonesia. This study aims to examine the influence of the Vespa Speeding Indonesia Channel on the lifestyle of its viewers, particularly young adults, and how this influence drives them to purchase a Vespa. The study focuses on the age group that watches and subscribes to the Vespa Speeding Indonesia Channel the most. Data was collected from 100 participants through a questionnaire distributed via Google Forms, and statistical analysis using a Likert scale was employed to analyze the data. The research utilized an explanatory quantitative analysis approach based on the SOR theory. The findings of this study indicate that the Vespa Speeding Indonesia Channel has a significant impact on the lifestyle of its subscribers.